2010
DOI: 10.1364/ao.49.001581
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of optical constants for uranium from 10 to 47 nm

Abstract: We use a laser high-harmonics-based extreme-ultraviolet (EUV) polarimeter to determine the optical constants of elemental uranium in the wavelength range from 10 to 47 nm. The constants are extracted from the measured ratio of p-polarized to s-polarized reflectance from a thin uranium film deposited in situ. The film thickness is inferred from a spectroscopic ellipsometry measurement of the sample after complete oxidation in room air. Uranium has been used as a high-reflectance material in the EUV. However, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The helicities alternate between harmonic orders, similar to the circular case (). Elliptically polarized high harmonics with fully tunable ellipticity may be useful for ultrafast spectroscopy and HG-based ellipsometry 47 . Notably, the fact that the ellipticity is determined by the DS makes it much more robust to perturbations than in other techniques 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The helicities alternate between harmonic orders, similar to the circular case (). Elliptically polarized high harmonics with fully tunable ellipticity may be useful for ultrafast spectroscopy and HG-based ellipsometry 47 . Notably, the fact that the ellipticity is determined by the DS makes it much more robust to perturbations than in other techniques 30 .…”
Section: Resultsmentioning
confidence: 99%
“…An elliptical DS () results in elliptically polarized eigenstates, and is useful for robust control of the ellipticity of all the high-order harmonics, collectively. These high harmonics would be useful for HG-based ellipsometry 47 . Furthermore, we explored non-collinear and solid HG and found that these include DSs that do not exist in the (2+1)D case: an inversion-time-translation DS that leads to odd-only harmonics (), an inversion-time-reversal DS that leads to linearly polarized harmonics (,), and improper-rotational DSs that lead to circularly/elliptically polarized high harmonics within the symmetry plane, and linearly polarized harmonics orthogonal to it ().…”
Section: Discussionmentioning
confidence: 99%
“…Our method could open up a wide range of applications in coherent control and ultrafast chiral spectroscopy for processes with narrow resonances and above 10 fs durations (e.g., X-ray magnetic circular dichroism measurements [27], and spin-flipping in magnetic materials [45]). Furthermore, it may find use in HHG-based ellipsometry [37]. …”
Section: Discussionmentioning
confidence: 99%
“…A hindrance for EUVL development is that the optical constants for many metallic materials in the EUV spectral range are not aptly determined. Inconsistencies are reported between different references for some materials [2,3]. In addition to the lack of calculated uncertainties for the optical constants of most materials, the accurate determination of the optical constants for materials becomes highly relevant for the development of next-generation EUVL optical components.…”
Section: Introductionmentioning
confidence: 99%